Mechanism of action of injectable depot contraceptives - Kesseru, Esteban (2015)
Several parameters were studied to clarity the mechanisms of action of two long-acting injectable contraceptive progrstins: 17-a-19-hydroxynorprogesterone caproate (which contraceptive effectiveness clinically lasts at least 8 weeks) and 19-norethindrone enanthate (effectiveness over 12 weeks). The "classic" theory of ovulation-inhibition was found uncovincing. In 14 ovarian biopsies of patients under treatment, taken in the second phase of the cycle, ovulation was evident in 11 of them by presence of corpora lutea. 245 endometrial biopsies showed that exogenus gestagen effect lasts only three weeks; after this period most endometria could be correlated with the cycle-day on which they were taken: 2/3 of these suggested biphasic cycles. Evaluation of 240 colpocytograms also confirmed endogenous cyclic activity. In order to explain the long-acting contraceptive effectiveness, cervical mucous factor has been thoroughly studied: in 380 cases spinnbarkeit (in cm.) and lerning (in %) were evaluated in correlation with the cycle-day and the time transcurred since the last dosis. A definitive gestagen effect, on the mucus, uniform and continous, was demostrated in contrast to the cyclic changes in the other parameters; this effect staris to decline simultanously with tle loss of contraceptive protection by the drug. The authors postulate that the cntraceptive effect to the two mentionned drugs are due to changes in the cervical factor that affect the sperm penetrability.